Riwayat Sukerta Sebuah Pengetahuan Kearifan Budaya Jawa - Sumanto Sumanto (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2007)
This article tries to describe the function and meaning of ruwatan for the Javanese. This is to answer the problem concerning ruwatan sukerta as a spiritual knowledge in Javanese culture. From the analysis, it can be found that ruwatan as one form of cultural events is neutral. It means that it can be used for any purpose; it depends on the arganizer motivation, for example, to increase prestige, to protect the ancestor tradition, as a purifying instruments, etc.The understanding or ruwatan as one of the cultural knowledge will be seen for example, from how people place themselves in the relation to the God, to other people, and tto nature and environment. Ruwatan is one form of beliefs so it depends oofn each individual. For the reason, it doesnâ€™t force anyone to believe.Â Key words: ruwatan sukerta, Javanese culture, a wise knowledge.